Emerging bicycle tourism and the theory of planned behavior. Issue 2 (1st February 2017) - Han, Heesup; Meng, Bo; Kim, Wansoo
ABSTRACT: In this study, we investigated the process of travelers' decision formation for bicycle touring as a form of sustainable tourism activity. We extended the theory of planned behavior (TPB), using personal norm and past behavior as predictors and the attractiveness of unsustainable alternatives as a moderator. Results of the modeling comparison showed that our extended TPB model was superior to the original TPB in predicting intention. Our results from the structural analysis revealed that the hypothesized paths linking attitude, subjective norm, perceived behavioral control, personal norm, and intention were supported; and personal norm significantly mediated the impact of subjective norm on intention. Moreover, our proposition that bicycle travelers' decision-making process would differ based on their level of the attractiveness of unsustainable alternatives was generally supported. Overall, our results help us clearly understand the role of volitional and non-volitional processes, personal norm, past behavior, and the attractiveness of unsustainable alternatives in explaining the intention formation of bike traveling.